Enfermedades más comunes en los niños de la escuela amauta Ñampi de Puyo. año 2013 -2014. - Mancilla Cuji, Carola Soledad (2015)
The following thesis aimed to the purpose of identifying the most common diseases in the school years of children from fourth to seventh grade in the bilingual school Amauta Ñampi located in the city of Puyo, province of Pastaza. This investigation was motivated by the fact that it has been seen the health problems that these kids show. The different deseases that the kids show are pediculosis, malnutrition and respitarory diseases thus affecting their academic performance and scholar disertion. It is important to mention that the children belong to the rural sector of the province and come from families of very low economic resources. It is through the nursing activities that the purpose of this research is to help to the well-being of every child. The design of the experiment was: non experimental type, explorative, descriptive, explanatory, bibliographic, quantitative, and qualitative and field work. The techniques used for the investigations were surveys to colect the data of this work as well as the observation: in the investigation was applied their respective instruments, the questionnaire and the observation guide. Various risk factors such as lack of sanitation, rural origin, lack of accessibility to homes and its various ethnicities and customs was evident. The conclusion was that children suffer from diseases such as pediculosis, low birth weight, and respiratory and diarrheal diseases. To make the intervention plan, the conclusions were based on the findings and recommendations, an educational plan in order to achieve a better knowledge about preventive measures to prevent infectious diseases